An Efficient and Secure Session Key Management Scheme in Wireless Sensor Network. (14th June 2021) - Mehmood, Gulzar; Khan, Muhammad Sohail; Waheed, Abdul; Zareei, Mahdi; Fayaz, Muhammad; Sadad, Tariq; Kama, Nazri; Azmi, Azri
Abstract : Wireless Sensor Network (WSN) is a particular network built from small sensor nodes. These sensor nodes have unique features. That is, it can sense and process data in WSN. WSN has tremendous applications in many fields. Despite the significance of WSN, this kind of network faced several issues. The biggest problems rising in WSN are energy consumption and security. Robust security development is needed to cope with WSN applications. For security purposes in WSN, cryptography techniques are very favorable. However, WSN has resource limitations, which is the main problem in applying any security scheme. Hence, if we are using the cryptography scheme in WSN, we must first guarantee that it must be energy-efficient. Thus, we proposed a secure hybrid session key management scheme for WSN. In this scheme, the major steps of public key cryptography are minimized, and much of the operations are based on symmetric key cryptography. This strategy extensively reduces the energy consumption of WSN and ensures optimum security. The proposed scheme is implemented, and their analysis is performed using different parameters with benchmark schemes. We concluded that the proposed scheme is energy-efficient and outperforms the available benchmark schemes. Furthermore, it provides an effective platform for secure key agreements and management in the WSN environment.